Assessment of special populations: Interventions against women and children victims of violence - Gumilang, Randi M.; Handari, Sai (Universitas Islam Negeri Raden Intan Lampung, 2020)
Assessment of Crucial Studies in an Effort to Protect Victims of Women's Opinions by the Integrated Service Center for Women and Children Empowerment (P2TP2A) as encouraging and focusing on problem assistance relating to women and children. The purpose of this study is to: (1) Describe and describe the use of assessment of interventions used by the Integrated Service Center for Women and Children Empowermen in East Kalimantan and; (2) Review the assessment of interventions used for women and children with special contributions by P2TP2A in East Kalimantan Province. This study uses descriptive qualitative research. Data collection techniques in this study used interviews, observation and documentation in various P2TP2A work areas in East Kalimantan Province. Includes areas of Samarinda, Bontang, East Kutai & Kutai Kartanegara. The results of this study, namely: 1) Assessment of interventions used in P2TP2A East Kalimantan Province consists of a combination that collects data that provides an overview of the case, service delivery process and service follow-up plans. The purpose of the assessment is to obtain an overview, process (formative) and outcome (summative). 2) The assessment used still consisted of conventional assessments that were widely adopted by P2TP2A in East Kalimantan. In some cases, there needs to be special handling, so the assessment used is based on the psychologist or medical history and other assessments that suit the needs of the client with special contributions.